Degradation performance and mechanism toward methyl orange via nanoporous copper powders fabricated by dealloying of ZrCuNiAl metallic glassy precursors. (7th January 2022) - Gu, Lingyu; Wang, Shushen; Hui, Xidong; Li, Fudong; Lin, Hengfu; Wu, Kaiming
Abstract: The catalyst of nanoporous Cu (NP-Cu) powders, with the chemical composition of Cu79.63 Ni6.85 O13.53 (at%), was successfully fabricated by dealloying of Zr–Cu–Ni–Al metallic glassy precursors. The as-prepared NP-Cu powders, co-existing with Cu2 O phase on Cu ligament surface, had a three-dimensional network porous structure. The NP-Cu powders/H2 O2 system showed superior catalytic degradation efficiency toward azo dyes in both acidic (pH 2) and neutral (pH 7) environments. Moreover, the cyclic tests indicated that this powder catalyst also exhibited good durability. A novel degradation mechanism of NP-Cu powders/H2 O2 was proposed: the high degradation performance in acidic environment was mainly derived from heterogeneous reaction involved with a specific pathway related to Cu 3+ to produce HO·, while in neutral environment it was primarily resulted from homogeneous reaction with the generation of HO· from the classical Cu-based Fenton-like process. This work indicates that the NP-Cu powders have great potential applications as catalysts for wastewater treatments.